Senyawa Disobinin yang Bersifat Antimalaria dari Biji Tumbuhan Chisocheton macrophyllus (Meliaceae) - Nurlelasari Nurlelasari; Desi Harneti PH; Unang Supratman (Study Program of Chemistry - Alauddin State Islamic University of Makassar, 2016)
Disobinin compounds have been isolated from the seeds Chisocheton macrophyllus (Meliaceae). The chemical structure of compounds disobinin identified based on data covering UV spectroscopy, IR, 1D-NMR, 2D-NMR and mass spectra as well as the comparison with the data obtained from the literature. Disobinin compound showed antimalarial effect against P. falcifarum with IC50 values from 0.001 to 0.01 mg/mL . Limonoids compound, disobinin reported for the first time in the genus of Chisocheton.